Sexism and its associated factors among adolescents in Europe: Lights4Violence baseline results. Issue 3 (21st February 2021) - Ayala, Alba; Vives‐Cases, Carmen; Davó‐Blanes, Carmen; Rodríguez‐Blázquez, Carmen; Forjaz, Maria João; Bowes, Nicola; DeClaire, Karen; Jaskulska, Sylwia; Pyżalski, Jacek; Neves, Sofia; Queirós, Sofia; Gotca, Ioan; et al.
Abstract: Despite the efforts of recent decades to reduce gender inequality, sexism is still prevalent among adolescents. The objective of this study was to identify the main socioeconomic characteristics, personal experiences, resources, and competencies associated with sexism in a sample of adolescents from different European countries. Baseline data from the Lights4Violence project included 1555 students ages 12–17 from secondary schools in six European countries (Spain, Italy, Romania, United Kingdom, Portugal, and Poland). Linear regression models were carried out, stratified by sex for benevolent (BS) and hostile (HS) dimensions of the Ambivalent Sexism Inventory. The average age of the sample was 14.3 years (SD = 1.5), 59.3% were girls. Boys scored higher on the measure of sexism (mean BS = 29.7; HS = 29.1) than girls (BS = 27.5, HS = 23.0; p < .001). Girls whose mothers had a university degree reported lower BS (β = −0.113; p = .023) (reference: lower education). Girls who had experienced dating violence reported higher HS (β = .080; p = .010) than those who had never been in an intimate relationship. For both sexes, high aggressiveness was associated with high levels of HS, and high aggressiveness was related to high levels of BS in boys. High assertiveness was associated with high levels of BS in both sexes and with high levels of HS in boys. A high level of problem‐solving ability was associated with lower HS in both sexes. The study reinforces the need to invest in school programs aimed at preventing dating violence and promoting positive youth development.